In vitro and in vivo activity of ML302F: a thioenolate inhibitor of VIM-subfamily metallo β-lactamases - Betts, J; Phee, L; Abdul Momin, M; Umland, K; Brem, J; Schofield, C; Wareham, D (Royal Society of Chemistry, 2015)
The thioenol ML302F was recently identified as an inhibitor of class B metallo-β-lactamases (MBLs). We assessed the activity of ML302F when combined with meropenem (MEM) against 31 carbapenem resistant Gram-negative clinical isolates. Minimum inhibitory concentrations of MEM:ML302F were determined at fixed ratios of 1:4 and 1 8 using strains producing variants of the clinically relevant VIM-like MBL. Toxicity and efficacy in vivo was assessed in a Galleria mellonella invertebrate model against strains producing VIM-1, VIM-2 and VIM-4 variants. At a fixed MEM:ML302F ratio of 1:8, 22/31 isolates were rendered either susceptible (MIC ≤ 2 mg L-1), or intermediate (MIC 4-8 mg L-1) to MEM. ML302F alone was not toxic at up to 80 mg kg-1 in G. mellonella and treatment with MEM 0.6 mg kg-1:ML302F 4.8 mg kg-1 significantly improved the survival of infected larvae. As ML302F was able to successfully restore susceptibility to resistant strains both in vitro and in vivo it represents a structurally interesting inhibitor in the search for new MBL inhibitors.